THE EFFECT OF USING SCAFFOLDING STRATEGIES ON STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT AT THE SEVENTH GRADE OF MTSN 6 AGAM - Nurcahaya Marpaung; Reflinda; Veni Roza; Melyann Melani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The research was determined to find The Effect Of Using Scaffolding Strategies On Students’ Reading Comprehension Of Descriptive Text At The Seventh Grade Of Mtsn 6 Agam. It was done at MTSN 6 Agam. The researcher found some problems, there were the students had limited vocabulary. Then, the students found it difficult to comprehend reading texts, which made them become passive learners in learning English. And the methods used by teacher in teaching are still not able to overcome the problems faced by students. In this research, the design of the research used the quantitative approach with experimental research design by using pretest-post test experimental and control group design. The population was seventh grade. To determine the sample the researcher used simple purposive sampling. The sample were VII.4 as the experiment class and VII.2 as control class. The result of the research indicates that the score of students in post test was higher than the score of pre test experiment. From the data the mean score of pre-test was 49.38, and than the mean score of students post-test was 72.8. 1t’s means these results suggested that the scaffolding strategy significant reading comprehension learning. In addition, from the calculation of the data The significance value (Sig. (2-tailed)) of 0.000, which is smaller than 0.05, indicates that there is a significant difference between the reading comprehension scores in the post-test of the control group and the post-test of the experimental group at MTSN 6 Agam of seventh grade by using scaffolding strategies to the students taught using conventional method. It can be concluded that, scaffolding gave significant effect for students in their reading comprehension.